2022
DOI: 10.1038/s41598-022-24065-0
|View full text |Cite
|
Sign up to set email alerts
|

Hot weather hazard analysis over India

Abstract: Heat waves are often termed as the silent killer and have become even more important as recent studies suggest that the heat wave have become second most devastating extreme weather events in terms of human deaths and losses. It is also been largely realised by scientific community that it is not just the high temperatures which are responsible for the gruesome effect of heat waves but several other meteorological parameters play a vital role in aggravating the impact and causing much more damages. In view of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…March month has shown higher 7) than the reference period. Some studies have also shown similar findings in India (Naveena et al, 2021;Chowdhury, 2022;Lekshmi and Chattopadhyay, 2022;Srivastava et al, 2022;Rathi et al, 2023;Rao et al, 2023). From figures 6a-d and 7a-d, this is clear that the March months' HWN/HWD is rising smoothly, while in July HW declined till the year 2000 and then rose again.…”
Section: Resultssupporting
confidence: 71%
“…March month has shown higher 7) than the reference period. Some studies have also shown similar findings in India (Naveena et al, 2021;Chowdhury, 2022;Lekshmi and Chattopadhyay, 2022;Srivastava et al, 2022;Rathi et al, 2023;Rao et al, 2023). From figures 6a-d and 7a-d, this is clear that the March months' HWN/HWD is rising smoothly, while in July HW declined till the year 2000 and then rose again.…”
Section: Resultssupporting
confidence: 71%
“…Heat waves are responsible for mortalities and have become the second most disastrous event. They further cause heat stress and are termed a silent killer (Srivastava et al, 2022). Urban heat island (UHI) is associated with the warming of an urban area about its surrounding rural area which tends to heatrelated diseases and mortality as it amplifies heat waves and unhealthy heat stress further (Chandra et al, 2022).…”
Section: Glimpse and Assessment Of Various Urban Risks And Their Asso...mentioning
confidence: 99%
“…Studies have tried to quantify the impact of different meteorological parameters in causing the heat stress in India. The regions with maximum cumulative heatwave hazard impact over the Indian region was found to be over Bihar, Jharkhand, Northeast and coastal regions such as West Bengal, parts of Odisha, northern part of south peninsular India and southern-most Tamil Nadu (Srivastava et al 2022).…”
Section: Introductionmentioning
confidence: 97%